Hubungan antara Pancasila dan demokrasi sebagai fondasi kehidupan berbangsa dan bernegara - Abdurrahim, Muhammad Fardhan (Maliki Interdisciplinary Journal, 2025)
Pancasila is the foundation of the state and the ideology of the Indonesian nation, serving as a guideline in every aspect of national and state life. Meanwhile, democracy is a system of government that provides space for the people to participate in the decision-making process. The two are closely related, with democracy in Indonesia being implemented based on the values ​​contained in Pancasila, rather than liberal or secular democracy. This paper aims to explain the role of Pancasila as the foundation of Indonesian democracy, analyze the relationship between the two in the practice of national life, and identify challenges and solutions in its implementation. The method used is a literature study from various sources such as laws, books, and scientific journals. The results of the discussion indicate that the values ​​of Pancasila strengthen Indonesian democracy through the principles of deliberation, unity, and social justice, thereby maintaining the stability and integrity of the nation. Thus, the implementation of democracy based on Pancasila is key to creating a harmonious and civilized national and state life.